Narrative Based Medicine and Neonatology: an interpretative approach - Massimiliano Zonza (Hygeia Press di Corridori Marinella, 2012)
The use of Evidence Based Medicine (EBM) has progressively lead doctors to focus their practice on the disease and not on the patient anymore. They consider a sick body or a sick part rather than a sick person. Such an attitude results in a progressive process of alienation or "unauthentic experience". On the contrary the Medical Humanities represents a strong reaction to this state of things, and for Medicine a chance to embrace again its humanistic "vocation". Narrative Based Medicine (NBM) places at the center of the clinical practice the communicative and relational dimension. This study deepen the application of NBM to the scope of neonatal care. As a result of our work, we have identified in the NBM applied to the neonatal area a fundamental characteristic, the Neonatal Triangle (doctors, patient, parents), and a triple functionality (diagnostic, ethical and educational) placed in three different ideal chronological moments (before, during and after). We explore the close connection between these functions and the clinical work and how the NBM model, through these same functions, enhance the opportunity of care and relationship. The main assumption is obviously the Doctors ability to build a shared narrative relation with the Parents of the little Patients, that in the technical terms of the Narrative Based Medicine is called co-construction of the illness history. We can remark that with the NBM we understand (the narrative frame), build (the therapeutic alliance) and share (decisions).